Determination of Force Factors During Precipitation - Fatkhulla Abdullaev; Xasan Ismailov; Shoxrux Akhmadayiev; Kamaliddin Khasanov (Research Parks Publishing LLC, 2021)
The paper represents analytical dependences of the precipitation process on the kinematically possible flow velocities that satisfy the boundary conditions and the condition of volume constancy.